Sleep, food cravings and taste. (1st June 2018) - Lv, Wen; Finlayson, Graham; Dando, Robin
Abstract: Objective: Taste is influenced by factors from our environment, psychology, and from our own physiological state. The objective of the study was to determine whether sleep influences our sense of taste or our cravings for food. Method: 57 healthy panelists, predominantly of college age, submitted to sleep tracking, and subsequently underwent a series of sensory tests, using basic prototypic tastants, as well as real foods. Panelists were also evaluated to quantify food cravings, using both the Leeds Food Preference Questionnaire, and the Control of Eating Questionnaire. Results: Umami (p = 0.025, F = 5.301) and sour (p = 0.037, F = 4.591) taste were intensified in those rating sleepiness higher, while this group also reported higher implicit wanting for high fat sweet foods (p = 0.011, Wald chi-sq = 14.937). Craving for sweet or savory also associated with a number of measures of taste response to real foods. Conclusions: Results imply that a lack of sleep may induce cravings for unhealthy foods, and that foods high in umami or sour taste may be experienced differently due to alterations in taste function. Results imply that feeding behavior may be influenced by a lack of sleep, acting at least partially through our sense of taste.